EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PANGAN DI DESA BILAPORAH, BANGKALAN - Slamet Supriyadi; Agus Imam Santoso; Achmad Amzeri (Universitas Trunojoyo Madura, 2009)
Land evaluation is a metode to evaluate the suitability of a land to certain use. The objective of this research was to determine land suitability class for food plants’ production. The methode apllied was FAO’s framework of land suitability classification, consisted of gathering the secondary data, soil survey to find out land characteristics, and matching between land qualities and the requirements of plant growth.The result of study revealed that first, land suitability for paddy was S2 (moderately suitable) with the limiting factors were annually temperature average, water availability, root zone condition, and nutrien availability. Second, the suitability for rainfed paddy was S3 (marginally suitable) with the main limiting factor was nutrien retention. Third, the suitability for maize and peanut, was S3 (marginally suitable) with the limiting factors were nutrien avalability and annually temperature average.